Unnificar : proposta de requalificação urbana em comunidades segregadas na cidade de Passo Fundo - RS - Zanoni, Carolina (2022)
Focused in the concept of urban integration, "Unnificar: Urban requalification proposal in segregated communities in the city of Passo Fundo - RS" brings solutions to improve quality of life from the population with the restructuration of infrastructure, adding green and lounge areas, urban equipament, security and dignified homes. The area is located next to important marks to the city of Passo Fundo and has great potential to integrate with the city through strategy's of social and espacial reintegration that were proposed.